Market engineering. A structured design process for electronic markets (2007)
In this book, the author provides a complete process for electronic markets design together with the required en-gineering methods. As such the book is unique applying tech-niques from engineering design to modern Information Systems and Economics. Mr. Neumann succeeds in presenting a generic but coherent approach that is an indispensable aid in designing markets.